Green innovations in the tourism sector - Gavrilović Zvjezdana; Maksimović Mirjana (Strategic Management, 2018)
Knowing that the tourism sector is able to generate significant social, economic and cultural benefits and development, looking for novel ways to improve this sector is more than justified. The tourism industry has not been immune to evolving advancements in Information and Communication Technologies (ICTs). Novel technology solutions and approaches have potential to significantly revolutionize this sector, making the vision of smart tourism omnipresent. Going further by investing in the greening of the tourism sector, sustainable, smart and green tourism will soon become reality. Protected environment and preserved cultural heritage and natural assets through the reduced usage of energy and reduced hazardous pollutants will consequently lead to economically, socially and environmentally sustainable tourism sector. These three components, green building, green energy and green waste are at the same time parts of the green management concept. Hence, to realize a vision of successful green tourism, it is essential to perform adequate green management implementations, including certain marketing efforts, namely green marketing. This paper presents an analysis of various greening processes of tourism sector with the help of ICTs and highlights the importance of green management and green marketing in achieving smart, green and sustainable tourism sector.